Next-Generation Sequencing of Carbapenem-Resistant Klebsiella pneumoniae Strains Isolated from Patients Hospitalized in the University Hospital Facilities - Ján Koreň; Michal Andrezál; Hana Drahovská; Zuzana Hubenáková; Adriána Liptáková; Tibor Maliar (MDPI AG, 2022)
Carbapenem-resistant (CR) Klebsiella pneumoniae represents an urgent worldwide threat. We focused on CR K. pneumoniae in selected facilities of the University Hospital Bratislava (UHB) to investigate sequence types (STs), clonal relatedness, and antimicrobial resistance. Suspected carbapenem-nonsusceptible K. pneumoniae strains were obtained from hospitalized patients. Further examination included carbapenemase confirmation, cgMLST, and quantitative susceptibility testing. Of the total 41 CR K. pneumoniae strains, 26 (63.4%) were determined as ST11 in hospital No. 1; of these ST11, 22 (84.6%) were found in the first internal clinic. Six (14.6%) ST258 and three (7.3%) ST584 occurred in hospital No. 2; the most, i.e., four (66.7%), ST258 were detected in the geriatric clinic. In hospital No. 3, we found two (4.8%) ST584 and one (2.4%) ST258. Of the ST11 set, 24 (92.3%) produced NDM-1. Furthermore, seven (87.5) ST258 and five (100%) ST584 strains generated KPC-2. Antimicrobial resistance was as follows: ertapenem 97.6%, meropenem 63.4%, tigecycline 7.3%, eravacycline 7.3%, and colistin 2.5%. We revealed a presumably epidemiological association of ST11 with transmission, particularly in the first internal clinic of hospital No. 1, while ST258 and ST584 were related to interhospital dissemination between medical facilities No. 2 and No. 3. It is essential to prevent the circulation of these pathogens within and between healthcare facilities.